2015
DOI: 10.18632/oncotarget.4453
|View full text |Cite
|
Sign up to set email alerts
|

An anti-EpCAM antibody EpAb2-6 for the treatment of colon cancer

Abstract: Epithelial cell adhesion molecule (EpCAM) is known to be overexpressed in epithelial cancers associated with enhanced malignant potential, particularly colorectal carcinoma (CRC) and head and neck squamous cell carcinoma (HNSCC). However, it is unknown whether progression of malignance can be directly inhibited by targeting EpCAM. Here, we have generated five novel monoclonal antibodies (mAbs) against EpCAM. One of these anti-EpCAM mAbs, EpAb2-6, was found to induce cancer cell apoptosis in vitro, inhibit tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 80 publications
2
37
0
Order By: Relevance
“…45,46 Additionally, a few studies using anti-EpCAM antibody showed that it might have an anti-tumour effect. [47][48][49] However, the validation of EpCAM as a therapeutic target remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Additionally, a few studies using anti-EpCAM antibody showed that it might have an anti-tumour effect. [47][48][49] However, the validation of EpCAM as a therapeutic target remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, antibody-binding could be harmful to cell survival. Some antibodies against EpCAM, for example, may directly cause cancer cell death [79] or indirectly induce antibody-dependent cell-mediated cytotoxicity (ADCC). Indeed, anti-EpCAM mediated cancer cell killing is a mechanism sought in studies involving adecatumumab, edrecolomab and catumaxomab.…”
Section: Technical Issues In the Various Ctc Isolation Methodsmentioning
confidence: 99%
“…Overexpression of EpCAM results in highly upregulated oncogene expression and promotes cell proliferation [ 16 ]. With the development of molecular technologies, EpCAM has gained attention as a potential target for diagnostic and antibody-based immunotherapies for a spectrum of malignancies [ 17 ]. The treatment improved the survival rate by 30% and decreased the recurrence rate by 27% over 7 years of evaluation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%